Analysis of the Appropriateness of Grammatical Rules in the Seventh-Grade Arabic Language Textbook of Junior High School Based on the Independent Curriculum - Nifa Mahfudotun Solehah; Moh Aman; Lukmanul Hakim (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
Teachers, as classroom role models, are required to demonstrate competence and creativity to foster effective interaction and support students' understanding during the learning process. In the Merdeka Belajar curriculum, textbooks serve as key learning media, including Arabic-language textbooks that cover linguistic rules. However, the unsystematic arrangement of these rules often limits students' ability to comprehend the intended grammatical concepts. This study aims to analyze the presentation of linguistic rules in a seventh-grade Arabic textbook and to evaluate their conformity to nahwu and sharf. Using a descriptive qualitative method supported by observation, analysis, and documentation, the study finds that the textbook's linguistic components are generally appropriate with respect to learning outcomes and content scope. Nevertheless, their alignment with classical Arabic grammatical principles is considered inadequate due to the absence of a systematic sequence in the presentation of the rules.